2013
DOI: 10.1002/app.40208
|View full text |Cite
|
Sign up to set email alerts
|

Toward environment‐friendly composites of poly(ε‐caprolactone) reinforced with stereocomplex‐type poly(l‐lactide)/poly(d‐lactide)

Abstract: In this work, stereocomplex-poly(L-and D-lactide) (sc-PLA) was incorporated into poly(e-caprolactone) (PCL) to fabricate a novel biodegradable polymer composite. PCL/sc-PLA composites were prepared by solution casting at sc-PLA loadings of 5-30 wt %. Differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD) demonstrated the formation of the stereocomplex in the blends. DSC and WAXD curves also indicated that the addition of sc-PLA did not alter the crystal structure of PCL. Rheology and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…PCL is characterized by a low melting point around 60 ºC, a very low glass transition temperature, T g at about -60 ºC; nevertheless, the thermal decomposition temperature is relatively high, with values around 350 ºC [16,17]. With regard to its mechanical properties, PCL is extremely ductile with a high elongation at break value and low modulus [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…PCL is characterized by a low melting point around 60 ºC, a very low glass transition temperature, T g at about -60 ºC; nevertheless, the thermal decomposition temperature is relatively high, with values around 350 ºC [16,17]. With regard to its mechanical properties, PCL is extremely ductile with a high elongation at break value and low modulus [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Moreover, the stereocomplexes could also form in its miscible or immiscible blends in solution conditions. [24][25][26][27] More recently, Yang and coworkers succeeded in preparing stereocomplex crystallites with high crystallinity and melting temperature by a novel and interesting low-temperature approach using high-molecularweight PLA that was difficult to achieve using conventional melt blending and solution casting methods. 28,29 The results demonstrated that exclusive stereocomplex crystallites without the homocrystallites of high-molecular-weight PLA could be formed at processing temperatures as low as 160 C, either at equimolar PLLA/PDLA blends or non-equimolar PLLA/PDLA (60 : 40) blends.…”
Section: Introductionmentioning
confidence: 99%
“…The flame‐retarding mechanism of PNFRs is generally divided into gas‐ and condensed‐phases . During the condensed‐phase, the thermal degradation of the flame retardant induces the generation of phosphoric acid, which promotes dehydration and liberates water during pyrolysis.…”
Section: Resultsmentioning
confidence: 99%